Principles of the integrated regenerative urban model and its application in the city of Santa Cruz de la Sierra – Bolivia - Ruiz Garvia, Ricardo (2022)
Integrated Regenerative Urbanism has gained importance in recent decades, presenting positive results in terms of adaptability and sustainability in different contexts. This article reviews, at the first instance, the background events in the global context, in order to determine its current significance. Consecutively, based on updated bibliography, the principles that allow the development of the model are documented. Subsequently, the different methods and strategies for its implementation are critically analyzed. Finally, the existing planning mechanisms in the city of Santa Cruz de la Sierra are identified, thus generating pertinent information for its possible implementation in the near future.